Adherence Analysis of Agile Methods According to the MR-MPS Reference Model - Arimoto, Maurício Massaru; Murakami, Edson; de Camargo, Valter Vieira; Cagnin, Maria Istela (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2009: Anais do VIII Simpósio Brasileiro de Qualidade de SoftwareDO - 10.5753/sbqs.2009.15516, 2009)
In this paper some preliminary guidelines are defined to assess the adherence of agile methods to the MR-MPS model by means of established metrics, taking into consideration the intrinsic characteristics of each one. As a case study, an analysis of the adherence of three agile methods (XP, Scrum and OpenUP) according to G and F levels of the MR-MPS was conducted, identifying the necessary changes and their impacts. The results of this analysis show that agile methods and maturity models may be compatible, although some differences were found. In this context, adjustments are proposed in agile methods, in order to make them more adherent at the G and F levels of the MR-MPS.